A retrospective study of the admission ways in the School of Dentistry of National Taiwan University from 2000 to 2021 - Feng-Chou Cheng; Ming-Chung Lee; Ling-Hsia Wang; Wen-Juain Lin; Tsui-Hua Liu; Shiang-Yao Liu; Chun-Pin Chiang (Elsevier, 2022)
Background/purpose: In Taiwan, dental schools have gradually become a popular choice for high school graduates to enter in the universities. This study mainly analyzed the various admission ways to enroll students into the School of Dentistry of National Taiwan University (SODNTU) from 2000 to 2021. Materials and methods: The data on the numbers of enrollees and those enrollees who had completed registration in the SODNTU from 2000 to 2021 were available online to the public and included in this study. Results: The total number of enrollees in the SODNTU over the past 22 years was 764 with an annual mean of 34.73. The registration rate ranged from 90.91% to 100% with a mean registration rate of 96.86% from 2000 to 2021. The examination admission, individual application admission, and numerous stars initiatives admission were the three main admission ways to enroll students into the SODNTU from 2000 to 2021 with a total of 662 enrollees (86.65% of a total of 764 enrollees). The number (proportion) of enrollees through examination admission showed a decreasing trend year by year from 26 (78.79%) in 2000 to 15 (45.45%) in 2021. On the contrary, those enrollees through individual application admission and numerous stars initiatives admission showed an increasing trend year by year from 4 (12.12%) in 2000 to 14 (42.42%) in 2021. Conclusion: Although the examination admission is still the predominant admission way, the individual application admission and numerous stars initiatives admission gradually play pivotal roles to enroll students into the SODNTU recently.